Relationship Between Pre-operative Blood Glucose Level and Length of Hospital Stay in Patients With Renal Cell Carcinoma Undergoing Laparoscopic Nephrectomy - He, Ting; Zhu, Weidong; Wang, Chunying; Lu, Haowen; Wu, Tiange; Pan, Kehao; Chen, Shuqiu; Xu, Bin; Mao, Weipu; Li, Wei; Chen, Ming (Frontiers in Surgery, 2021)
Purpose: The aim of this study was to assess the effect of pre-operative blood glucose (POBG) levels on the length of stay (LOS) in patients with renal cell carcinoma (RCC) undergoing laparoscopic nephrectomy. Methods: We collected clinical data on 338 patients with RCC who underwent laparoscopic nephrectomy between 2014 and 2019. Univariate and multivariate logistic regression and dose-response analysis curves of restricted cubic spline function were used to investigate the relationship between POBG and LOS. Results: According to the level of POBG, we divided the patients into three groups: <4.94 mmol/L group, 4.94 to <7.11 mmol/L group, and ≥7.11 mmol/L group. According to the dose-response analysis curves, we found that the adjusted risk of LOS > 2 weeks and LOS > 3 weeks gradually increased with increasing POBG. In addition, we found that among all patients, patients with POBG levels ≥ 7.11 mmol/L had a 115% higher risk of LOS > 2 weeks than patients with POBG levels <4.94 mmol/L [adjusted odds risk (aOR) 2.15; 95% CI 1.11-4.20; p = 0.024] and patients with POBG levels ≥ 7.11 mmol/L had a 129% higher risk of LOS > 3 weeks than patients with POBG levels <4.94 mmol/L (aOR 2.29; 95% CI 1.16-4.52; p = 0.017). Moreover, similar results were observed in the most subgroups analysis. Conclusion: We found that in patients with RCC undergoing laparoscopic nephrectomy, higher POBG levels were significantly associated with prolonged LOS.